Tinjauan Literatur Kombinasi Strategi Biaya Rendah–Diferensiasi–Fokus Pada Perusahaan Startup - Cantika Dewi Apriyani; Dimas Fernando; Hesti Kusumaningrum (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This article reviews literature on implementing Porter’s generic strategies – cost leadership, differentiation, and focus – and their combinations in startup companies. The aim is to assess the alignment of the article’s content with the focus on combinational strategies. The study employs a systematic qualitative literature review, collecting and analyzing recent (2015–2025) academic articles and case studies related to startup business strategies. The findings indicate that differentiation and focus strategies are generally more effective at driving competitive advantage for startups than a lone cost-leadership approach. Integrating differentiation with cost leadership can create synergies of added value and operational efficiency. For example, some culinary ventures combine unique product attributes with cost control to attract customers. In conclusion, startups are advised to align their strategic choices with market characteristics and consider hybrid strategies to build sustainable competitive advantage.